Establishment of Optimum Processing Conditions for Some Technological Manganese-Zinc Ferrites - Tamin, Rohaida (2002)
This research work is an initial step to produce manganese-zinc ferrites in the laboratory using the solid-state ceramic preparation method with controlled atmospheres. The first part of the work was to develop the required material by manipulation of composition. Then, the specimens were sintered at 1350°C in an oxygen partial pressure. At this stage, a systematic crucial approach was used to produce high permeability ferrites with suitable oxygen partial pressure. This involved a gradual introduction of nitrogen gas into the furnace during sample cooling giving an optimum equivalent isocompositional line. This work has successfully produced materials (samples MRQI and MRQ2) suitable with the permeability in the range of 2000 to 2500 when an average particle size was reduced to ~2.5µm and zinc oxide was added to minimize zinc loss. Then the sintering cycle was made to follow the isocompositional line In conclusion an optimum processing technique has been established for producing ferrite materials with the desired magnetic properties.